Comparative analysis of two maritime routes in part of North America in the context of global warming, melting ice caps and opening of new passages for navigation - Dinu, Atodiresei (Scientific Bulletin ("Mircea cel Bătrân" Naval Academy), 2020)
The subject of this paper is to analyze comparative two maritime routes planned different for a ship that carry cargo from the United Kingdom to the Norton Sound, (63o 48’N / 161o21’W). The route are analyzed separately as a result of the evolution of the thermal regime, the ice in the last ten years in the area of North America and the impact of ice caps, from the perspective of total distance and opportunity of navigation. Take into consideration all three possible routes on this date, only the north-west route was included in this comparative analysis. The results presents a difference of 6070 Nm between the classic route (using Panama Channel) and the route through north-west passage, in safety condition.